An Analytical Study of the Management of Iraq’s Oil Revenues With Reference to the Norwegian Model - Yasin Abed Salh; Saad Hassan Ali (Journal of Madenat Alelem University College, 2020)
The success of the development of oil revenues and activation requires that there be a set of elements and the most prominent provide security and political and economic stability and clarity of political and economic vision of the Iraqi government and transparency in the management of economic resources, whether oil or non-oil revenues, the announcement of the allocations of each ministry and the aspects of this allocation and areas in addition to the formation of committees to oversee spending in the fields of investment or reconstruction or any other field, subject the work of these committees to oversee, control and audit and encourage oil investments in accordance with conditions that do not prejudice the sovereignty and interest of the country, such as tax exemptions total or partial, allow the transfer of profits realized outside the country according to agreed limits. It is also appropriate to follow Norway’s model in establishing a sovereign fund which considered as leading development experience in oil revenue management taking into account that the Iraqi economy still needs to continue to build infrastructure, development human capital through education, health and job creation.